2010
DOI: 10.1038/ijo.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

The chronobiology, etiology and pathophysiology of obesity

Abstract: The effect of CD on human health is an emerging issue. Many records link CD with diseases such as cancer, cardiovascular, cognitive impairment and obesity, all of them conducive to premature aging. The amount of sleep has declined by 1.5 h over the past century, accompanied by an important increase in obesity. Shift work, sleep deprivation and exposure to bright light at night increase the prevalence of adiposity. Animal models have shown that mice with Clock gene disruption are prone to developing obesity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
1
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(179 citation statements)
references
References 133 publications
(168 reference statements)
3
165
1
10
Order By: Relevance
“…In relation to clock genes, numerous studies performed in experimental animals with mutations in clock genes have proved that there is a relation between these mutations and further failures in circadian system and illness. In this sense, animals with mutations in clock genes show a higher risk of developing certain diseases, such as CVD, cancer and obesity (5) . One of the first studies which showed the effect of genetic mutations on chronic illnesses was conducted in 2005 by Turek et al (6) This study proved that homozygous Clock mutant mice were hyperphagic and obese, displayed adipocyte hypertrophy and developed metabolic syndrome (MetS).…”
Section: Failures In the Central Clock: Mutations In Experimental Animentioning
confidence: 99%
“…In relation to clock genes, numerous studies performed in experimental animals with mutations in clock genes have proved that there is a relation between these mutations and further failures in circadian system and illness. In this sense, animals with mutations in clock genes show a higher risk of developing certain diseases, such as CVD, cancer and obesity (5) . One of the first studies which showed the effect of genetic mutations on chronic illnesses was conducted in 2005 by Turek et al (6) This study proved that homozygous Clock mutant mice were hyperphagic and obese, displayed adipocyte hypertrophy and developed metabolic syndrome (MetS).…”
Section: Failures In the Central Clock: Mutations In Experimental Animentioning
confidence: 99%
“…Although mostly cross-sectional, the association of job stress or strain with obesity supports an important conceptual model involving exercise behavior/activity, job stress (38, 111, 114). Shift work, sleep deprivation, and exposure to bright light at night have been associated with increased adiposity (115). Cross-sectional studies suggest that disrupting normal eating and sleeping patterns through night shift work or rapidly rotating day/night shifts are risks for obesity and metabolic syndrome (116).…”
Section: Example 23mentioning
confidence: 99%
“…In newborns and infants, delayed circadian maturation may be caused by an early deficiency in exposure to environmental synchronizers or by impaired neural development (Rivkees 2003). In adults and older people, circadian disruption is associated with increased morbidity and mortality due to aging and certain pathologies, such as metabolic syndrome, cancer, cognitive and affective disorders, sleep impairment, and cardiovascular events (Garaulet et al 2010;Reiter et al 2007). Thus, the development of reliable and noninvasive means to assess CS functionality in subjects in their own home environment has become an imperative.…”
Section: Introductionmentioning
confidence: 99%